PENGARUH PARTISIPASI MASYARAKAT DESA HUTAN DALAM PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT (PHBM) TERHADAP KESEJAHTERAAN MASYARAKAT DESA HUTAN (STUDI KASUS DI BKPH KLUMO BANGSRI KABUPATEN JEPARA) - Naila Izzah; Edi Santosa; Hermini susiatiningsih (Journal of Politic and Government Studies, 2014)
AbstractThe essence of Forest Community Resource Management (FCRM) is giving space forest villagers to participate in the management of forest resources for the public welfare forest village. Thus of the theories that have been presented in the study show that the participation of forest villagers in FCRM have an influence on the public welfare forest villager The results of empirical tests on the effect of forest villagers participation BKPH Klumo Bangsri Jepara in Forest Community Resource Management (FCRM) on the welfare of forest villagers BKPH Klumo Bangsri Jepara shows that community participation in Forest Community Resource Management (FCRM) effect on the public welfare forest village. The results showed reject H0 and accept Ha which states "There is a significant effect influence the participation of forest villagers in the Forest Community Resource Management (FCRM) on the public welfare forest villager ". There is a positive relationship between the variables of forest villagers participation in Joint Forest Resource Management (CBFM) and the public welfare forest village included in the category of pretty or moderate and independent variables were able to explain the dependent variable of 33.8%, while the remaining 67.2% described other variables not included in this model (not examined). The coefficient of determination of test results provide meaning, that there are other independent variables that influence the public welfare forest villager.Keyword : Forest Community Resource Management (FCRM), the participation of forest villagers, and the public welfare forest villager.